Ethics and business : an introduction - Gibson, Kevin (Cambridge applied ethics, 2023)
This updated introduction to business ethics offers a clear and accessible framework for understanding the important and complex ethical issues facing business in the contemporary world. Kevin Gibson explains ethical concepts in plain language, showing how terms such as responsibility, autonomy, justice, equality, rights, and beneficence are central to the ways in which business is and should be conducted. He provides numerous examples and discusses cases including VW, Wells Fargo, the Boeing 737 Max, and the exploitation of rare earth minerals, and he pays special attention to recent and emerging issues such as the gig economy, internet commerce, racial and gender justice, and concerns about the impact of business on global climate change. His lively and comprehensive book will give readers the tools to identify and understand a range of problematic ethical issues that affect us all.
Keywords: yritykset; etiikka; arvot (käsitykset); yritysetiikka; sosiaalinen vastuu; yhteiskuntavastuu; voitot (talous); ympäristövastuu; globalisaatio; Business ethics; Social responsibility of business; Corporate profits : Moral and ethical aspects; Business enterprises : Environmental aspects; Globalization : Moral and ethical aspects